Effect of Nilvadipine on the Cerebral Ischemia-Induced Impairment of Spatial Memory and Hippocampal Apoptosis in Rats - Katsunori Iwasaki; Kenichi Mishima; Nobuaki Egashira; Izzettin Hatip Al-khatib; Daisuke Ishibashi; Keiichi Irie; Hirotoshi Kobayashi; Takashi Egawa; Michihiro Fujiwara (Elsevier, 2003)
ABSTRACT: We investigated the effects of nilvadipine and amlodipine on the cerebral ischemia-induced impairment of spatial memory in 8-arm radial maze performance and hippocampal CA1 apoptosis in rats. Single cerebral ischemia impaired memory without inducing apoptosis. In these rats, neither nilvadipine nor amlodipine at 3.2 mg/kg, i.p. improved the impaired memory. On the other hand, repeated cerebral ischemia (10 min ischemia × 2, 1 h interval) impaired spatial memory and induced hippocampal apoptosis 7 days after the final occlusion/reperfusion. Moreover, repeated ischemia increased the apoptotic cell number, an effect observed after 3 days and peaked after 7 days. However, mRNA expression of the apoptosis-related early oncogene bax and CPP 32 (caspase-3) was observed after 24 h. In these rats, nilvadipine, but not amlodipine, significantly improved memory, concomitantly decreased hippocampal apoptosis, and suppressed both bax and CPP 32 expression. These results suggest that nilvadipine improved the memory impairment in repeated ischemia by reducing bax and CPP 32 expression and suppressing the induction of apoptosis in the hippocampus. Nilvadipine may have a neuroprotective effect and could be a useful pharmacotherapeutic agent for cerebrovascular dementia.